The fractious stability of an immoral landscape. The land walls of Istanbul, 1910 to 1980. - Strutz, Julia; Neumann, Christoph K. (Routledge, 2021)
Throughout the past century, the city of Istanbul and its inhabitants have been discussed as imperfect. Istanbul came to be regarded as ignoble to its heritage. The Theodosian land walls are an interesting case to explore this phenomenon. This monumental landscape has come to symbolize the Istanbul of the immoral. Plus, it quite literally housed the illicit, the informal and the dangerous: Roma, prostitutes, tramps, minorities, migrants and others. This chapter takes space seriously as an element of governmental self-formation. It investigates the role that the Istanbul land walls have played in forming the imagination of a good urban citizen throughout the past century. It examines different ethical discourses in the period between 1910 and 1980. The period between 1910 and 1953 stands for an ethics of demolition and civilization, especially in comparison with “the West”. The time 1953 to 1983 tells the formation of the “bad” Istanbulite in the face of little regulated migration to Istanbul, and developmental economic policy.
Keywords: Stadtgeschichte; Stadtlandschaft; Stadtmauer; Stadtrand; Zivilisation; Nationalismus; Kulturerbe; Lebensform; Stadtbild; Soziale Randgruppe; Landflucht; Squattersiedlung